Innovation and change in northern Australian Aboriginal spear technologies: the case for reed spears. (April 2015) - Allen, Harry; Akerman, Kim
Abstract: Unlike the majority of spears used by Australian Aboriginal people, reed spears were a lightweight form that made optimal use of spearthrower technology. In the Kimberleys, reed spears were mounted with small pressure‐flaked stone projectile points. Small projectile points occur in the archaeological record of both the Kimberleys and western Arnhem Land. Outside the Kimberleys, however, there is no record of how these were mounted and used. This paper reviews the evidence for reed spears and small projectile points across the Northern Territory and north‐western Western Australia, concluding that they represent associated technologies the primary role of which lay in feuding and conflicts.